Preliminary Study on Air Traffic Density of Peninsular Malaysia using Visual Flight Path Trajectories from Automatic Dependent Surveillance-Broadcast (ADS-B) Data - Mustaffa, Masnawi; Ahmad2, Shaharudin; Mohd Nor, Radhiah; Hidayah Binti Zahari, Nur (International Journal of Engineering and Technology, 2018)
Automatic Dependent Surveillance-Broadcast is an alternate method of providing aircraft position data, which aircraft continually transmit their identity and navigational information. Such signals are received by ground station and relayed to Air Traffic Services and used to supplement radar data. The information can also be received by other aircraft and the nearby traffic. In this study, the ADS-B data was collected from a known website in order to investigate the movements of aircraft flying over Peninsular Malaysia's airspace by plotting the trajectories of flight path based on its flight ID, latitude, longitude, and altitude information. From flight trajectories and flight path of all collected data, the density and flow of air traffic from the ADS-B system for Peninsular Malaysia can be visualized.Â